Halophyte-derived nanoparticles and biostimulants for sustainable crop production under abiotic stresses - Rekha Agrawal; Soumya Koippully Manikandan; Maria Hasnain; John Klironomos; Mohamed S. Sheteiwy; Ali El-Keblawy (Plant Stress)
Global agriculture faces escalating challenges from multiple abiotic stresses, including salinity, drought, heavy metal toxicity, and rising temperatures. These factors collectively threaten crop yields and food security. Halophytes, inherently adapted to extreme environments, offer valuable insights into stress tolerance mechanisms and serve as promising sources for nanoparticle (NPs) and biostimulant development. NPs have high surface reactivity and controlled release capabilities that enable them to enhance nutrient-use efficiency, strengthen antioxidant defenses, and mitigate ion toxicity under adverse conditions. Biostimulants derived from halophytes complement NP applications by activating internal defense pathways which further optimize osmotic balance, promote root development and interaction with beneficial microbes. This review explores the increasing research on halophyte-based NPs and biostimulants, highlighting their diverse roles in reducing salinity, drought, heavy metal pollution, and heat stress and their possible applications in waste management. Emphasis is placed on phytonanotechnology, an eco-friendly synthesis method leveraging the inherent biochemical properties of halophytes, and on strategies for the integrated use of NPs and biostimulants to augment crop resilience. This review articulates how halophyte-driven innovations can address urgent agricultural and environmental needs by examining both mechanistic insights and field-level implications. It also highlights critical knowledge gaps, notably in large-scale testing, product standardization, and safety assessments. Overall, the synergy between halophyte biostimulants and NPs provides a potent toolkit for modern, climate-smart agriculture, poised to benefit plant productivity, ecosystem health, and resource efficiency.